PENGARUH STRATEGI PEMBELAJARAN DEEP DIALOGUE DAN KEMAMPUAN AWAL TERHADAP PEMAHAMAN MATERI KULIAH TEORI BELAJAR DAN PEMBELAJARAN - C. Asri Budiningsih (Jurnal Penelitian Ilmu Pendidikan, 2010)
The selection of instructional strategy is very important considering that students' characteristics are varied and the allocation of lecturing time is limited. Students of the educational technology department show dissatisfied results in learning and instruction theory. Students who don't possess the sufficient comprehension ability will experience difficulties in achieving the higher abilities such as synthesis, analysis, and evaluation. This research was conducted to verify whether the deep dialogue instructional strategy and the student's prior knowledge give different impacts toward the materials' comprehension or not. This research utilized quasi experimental design by non-equivalent control group design planning 2x2 factorial version. Research subjects were the students of Educational Technology department, FTP UNY, who took the Learning and Instruction Theory. The students consisted of two classes, class A (44 students) as experimental group, and class B (41 students) as the control group. Research tools utilized were: 1) Instrument to execute the deep dialogue Instructional Strategy, 2) Student's comprehension instruments, and 3) Student's prior knowledge instrument. Data's compilation was conducted in steps; 1) pretest, 2) learning treatment, and 3) post-test. Data analysis technique was done descriptively and by ANOVA factorial of 2 x 2. The results of research showed that; 1) there were no significant differences, of material comprehension level between the students who experienced deep dialogue instructional strategy with the students who performed the oral learning strategy, presentation and interactive conversation, 2) there were no distinct differences on the student's comprehension level to understand the delivered materials between the students who possessed high prior knowledge with the low prior knowledge students, 3) there were no interactions occurred in the utilization of deep dialogue instructional strategy with the student's initial comprehension ability to understand the delivered materials. Keywords: Deep Dialogue Instructional Strategy, Prior Knowledge